Effect of functionalized graphene oxide with hyperbranched POSS polymer on mechanical and dielectric properties of cyanate ester composites. Issue 45 (19th April 2016) - Zhang, Mengmeng; Yan, Hongxia; Yuan, Lingxia; Liu, Chao
Abstract : Functionalized graphene oxide with a hyperbranched POSS polymer was designed and synthesized and then compounded with dicyclopentadiene bisphenol dicyanate ester to prepare nanocomposites. Abstract : In this paper, a hyperbranched silsesquioxane polymer grafted graphene oxide (HPP-GO) was fabricated successfully. Hexamethylenediamine was firstly grafted onto the graphene oxide sheets. Then chloropropyl silsesquioxane and hexamethylenediamine were repeatedly grafted onto the hexamethylenediamine coated graphene oxide, which was confirmed by X-ray photoelectron spectroscopy, Fourier-transform infrared spectra, X-ray diffraction and transmission electron spectroscopy. Subsequently, the HPP-GO was incorporated into dicyclopentadiene bisphenol dicyanate ester (DCPDCE) to prepare composites. The effects of HPP-GO on the mechanical, dynamic mechanical, dielectric and thermal properties of DCPDCE resin were investigated systematically. Results show that the appropriate content of HPP-GO can enhance the mechanical properties including impact and flexural strengths of DCPDCE resin. When HPP-GO content is 0.6 wt%, the corresponding composite exhibits higher storage modulus, glass transition temperature and onset degradation temperature values than pure DCPDCE resin. In addition, the dielectric constant and loss of HPP-GO/DCPDCE composites are decreased with the increasing content of HPP-GO. These attractive properties of HPP-GO/DCPDCE composites suggest that the method proposed herein is effective to prepare high-performance graphene oxide/polymer composites.